Cluster heatmap for screening the drought tolerant rice through hydroponic culture. Issue 4 (July 2021) - Sakinah, A I; Musa, Y; Farid, M; Anshori, M F; Arifuddin, M; Laraswati, A A
Abstract: The development of drought rice screening is one of the keys to increase selection effectiveness. This development can be done by developing the analytical method. In general, identification of tolerant rice can be conducted with the cluster analysis. However, the common cluster analysis just was focused on genotype clusters so that the reason for the clustering does not can explain. Therefore, the other analysis approach needs to be done, such as cluster heatmap analysis. The objective of this study is to identify the effectiveness of cluster heatmap used in rice tolerance screening under drought stress. This study was designed with a nested randomized complete group design, where replications were nested in PEG 6000 concentration as a screening environment. The concentration of PEG used in this study was 0% PEG and 20% PEG. The genotype used consisted of 8 genotypes repeated three times. Hydroponic culture used ABmix in culture solution. As for, the number of characters observed was seven morphology characters and three physiological characters. The results of this study showed that cluster heatmap analysis could distinguish between the rice tolerant group drought-tolerant variety control (Salumpikit, Pokkali, and Inpari 29), and sensitive variety control (IR 20). Besides that, the good selection characters in hydroponic drought screening were shoot length, the number of tillers, shoot fresh weight, root fresh weight, and total biomass fresh weight. Based on this study, the cluster heatmap can be recommended as one of the analytical methods in hydroponic drought screening.